Relationship between adolescent internet addiction and adolescent non-suicidal self-injury: a moderated mediation model - Liu, Nan; Li, Huaxiang; Wang, Lin; Yin, Jiemei; Peng, Aiqin (Frontiers in Psychiatry, 2024)
Background Both Internet addiction (IA) and non-suicidal self-injury (NSSI) are major public health concerns among adolescents, association between internet addiction and non-suicidal self-injury have been observed among adolescents. However, it is unclear how, and under what conditions, internet addiction relates to non-suicidal self-injury. According to our hypothesis, there is a positive relationship between IA and NSSI among Chinese adolescents, but this relationship is affected by the mediating role of loneliness and the moderating role of cognitive reappraisal. Method A cross-sectional survey was conducted on 1046 Chinese adolescents from 3 middle schools. Measurements: Adolescent Self-Harm Scale; Young’s Internet Addiction Test (IAT); University of California at Los Angels (UCLA) Loneliness Scale; Emotional Regulation Questionnaire (ERQ), They were asked to complete self-report questionnaires. Results In our sample, the detection rate of NSSI was 12.3%. IA was positively associated with NSSI, and loneliness partially mediated the association between them. In addition, cognitive reappraisal moderated the first half path of the mediation model. Specifically, the higher the level of cognitive reappraisal, the weaker the positive effect of IA on NSSI through loneliness. Conclusion Interventions targeted to reduce loneliness and increase cognitive reappraisal strategies may reduce the risk of NSSI in adolescents with Internet addiction.